Beginning Google Web Toolkit - Smeets, Bram (Apress, 2012)
Over the last couple of years, we’ve noticed that our customers have gotten more demanding when it comes to the usability of their web applications. Inspired by the “web 2.0” trend and applications such as Gmail and the like, we’ve tried many approaches to building these rich Internet applications (RIAs). But all of these had one big flaw: they required us to learn a different language, including adhering to a whole new set of conventions and best practices. Only with the introduction of Google Web Toolkit (GWT) have we begun to feel confident about building this kind of application in a maintainable fashion. This book introduces GWT within the context just described, and will guide you through the first steps of using it to build real-world applications. The goal is to get you as a Java developer up to speed quickly by providing just enough background and a lot of hands-on code samples. During the course of the book, we’ll guide you through the different aspects of GWT that we feel are important, and leave out the ones we feel are out-of-scope for beginners. Most of the code samples will gradually build to make up a real-world sample application that allows you to manage your tasks using a web application. After reading this book, you’ll be equipped with the necessary knowledge and tools to start building real-world applications using GWT.